Engineering Trehalose Synthesis in Lactococcus lactis for Improved Stress Tolerance - Carvalho, Ana Lúcia (American Society for Microbiology, 2011)

(untitled)
Trehalose accumulation is a common cell defense strategy against a variety of stressful conditions. In particular, our team detected high levels of trehalose in Propionibacterium freudenreichii in response to acid stress, a result that led to the idea that endowing Lactococcus lactis with the capacity to synthesize trehalose could improve the acid tolerance of this organism. To this end, we took advantage of the endogenous genes involved in the trehalose catabolic pathway of L. lactis, i.e., trePP and pgmB, encoding trehalose 6-phosphate phosphorylase and β-phosphoglucomutase, respectively, which enabled the synthesis of trehalose 6-phosphate. Given that L. lactis lacks trehalose 6-phosphate phosphatase, the respective gene, otsB, from the food-grade organism P. freudenreichii was used to provide the required activity. The trehalose yield was approximately 15% in resting cells and in mid-exponential-phase cells grown without pH control. The intracellular concentration of trehalose reached maximal values of approximately 170 mM, but at least 67% of the trehalose produced was found in the growth medium. The viability of mutant and control strains was examined after exposure to heat, cold or acid shock, and freeze-drying. The trehalose-producing strains showed improved tolerance (5- to 10-fold-higher survivability) to acid (pH 3) and cold shock (4°C); there was also a strong improvement in cell survival in response to heat shock (45°C), and no protection was rendered against dehydration. The insight provided by this work may help the design of food-grade strains optimized for the dairy industry as well as for oral drug delivery.